2014
DOI: 10.3171/2013.9.spine121081
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between biomechanical changes at adjacent segments and number of fused bone grafts in multilevel cervical fusions: a finite element investigation

Abstract: Object Biomechanical studies have shown that anterior cervical fusion construct stiffness and arthrodesis rates vary with different reconstruction techniques; however, the behavior of the adjacent segments in the setting of different procedures is poorly understood. This study was designed to investigate the adjacent-segment biomechanics after 3 different anterior cervical decompression and fusion techniques, including 3-level discectomy and fusion, 2-level corpectomy and fusion, and a corpectomy-discectomy hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…As indicated in the present finite element study, ACDF impairs normal cervical biomechanics, alters mechanics at adjacent segments, resulting in higher stress and hypermobility in adjacent segments. Our results are in line with the reported data of the biomechanical studies on the behavior of the adjacent segments in the setting of different operation procedures [49][50][51][52][53]. Both the present and all of the reported results suggested that ASD might be related to iatrogenic biomechanics.…”
Section: Discussionsupporting
confidence: 92%
“…As indicated in the present finite element study, ACDF impairs normal cervical biomechanics, alters mechanics at adjacent segments, resulting in higher stress and hypermobility in adjacent segments. Our results are in line with the reported data of the biomechanical studies on the behavior of the adjacent segments in the setting of different operation procedures [49][50][51][52][53]. Both the present and all of the reported results suggested that ASD might be related to iatrogenic biomechanics.…”
Section: Discussionsupporting
confidence: 92%
“…Our study focused on patients undergoing central corpectomy, which is known to produce increased biomechanical stresses on the adjacent segments, 9 as well as reduced cervical lordosis and segmental height, 19,21 as compared with anterior cervical discectomy and fusion. The range of motion of adjacent segments after central corpectomy changes significantly after surgery, particularly at the inferior adjacent segment.…”
Section: Discussionmentioning
confidence: 99%
“…[16, [20][21][22][23]. Ligaments were simulated using springs subject to only pullout force [ The number of nodes and elements of the model is re ected in the following gure [Table 4] [Fig.…”
Section: Grid Division and Boundary Condition Settingmentioning
confidence: 99%